Synthesis of high molecular weight linear and branched polylactides: A comprehensive kinetic investigation. (November 2015) - Karidi, Konstantina; Mantourlias, Theofanis; Seretis, Antonios; Pladis, Prokopios; Kiparissides, Costas
Graphical abstract: Highlights: The ROP ofl, l -lactide in the presence of polyalcohols is investigated. Experimental results on polymerization rate and MWD for different co-initiators. Assessment of the hydroxyl groups reactivity for different polyalcohols. High molecular weight linear and non-linear polylactides were synthesized. Tailor-made PLLA was synthesized with desired end-use properties. Abstract: High molecular weight polylactides were synthesized in melt, via the ring-opening polymerization ofl, l -lactide, in the presence of stannous octoate Sn(Oct)2 as initiator and 1, 4-butanediol, glycerol, di(trimethylolpropane) (DTMP) and polyglycidol (PG) as co-initiators. The polymerization kinetics (i.e., time evolution of monomer conversion and molecular weight distribution) as well as the effect of monomer to co-initiator (i.e., [M]/[CI]) molar ratio on the polymerization rate and the average molecular properties (i.e., M n and M w ) of polylactides were examined. It was shown that at high concentrations of 1, 4-butanediol and glycerol the ring-opening polymerization ofl, l -lactide followed closely the kinetics of an "ideal living" polymerization. In addition, the relative reactivity of the hydroxyl groups of the selected co-initiators was assessed in comparison to the reactivity of water hydroxyl groups measured in the absence of a co-initiator. The synthesized polylactides were fully characterized with respect to their molecular, thermal and mechanical properties. It was found that the synthesized branched polylactides exhibited significantly different thermal and mechanical properties than the linear PLAs.